Care patterns and Traditional Chinese Medicine constitution as factors of depression and anxiety in patients with systemic sclerosis: A cross-sectional study during the COVID-19 pandemic - Kong, Qi; Chen, Li-Ming; Dai, Zong-Hao; Tang, Yun-Zhe; Zhou, Yu-Yang; Tu, Wen-Zhen; Zhao, Yin-Huan; Zhang, Jia-Qian (Frontiers in Integrative Neuroscience, 2023)
Objective: Care patterns and Traditional Chinese medicine (TCM) constitution affects the emotion and health of patients with systemic sclerosis (SSc) while the prevalence of COVID-19 may aggravate such patients’ emotion and health. We investigated the depression and anxiety levels of patients with SSc during the pandemic to identify the correlation between care patterns, TCM constitution, and patients’ emotion. Methods: This was a cross-sectional study. Patients with SSc and healthy individuals were surveyed using the patient health questionnaire-9, generalized anxiety disorder-7, and constitution in Chinese medicine questionnaire and a modified care pattern questionnaire. Factors correlated with depression and anxiety were screened using univariate and multivariate logistic regression analyses. Results: A total of 273 patients with SSc and 111 healthy individuals were included in the analysis. The proportion of patients with SSc who were depressed was 74.36%, who had anxiety was 51.65%, and who experienced disease progression during the pandemic was 36.99%. The proportion of income reduction in the online group (56.19%) was higher than that in the hospital group (33.33%) (P=0.001). Qi-deficiency (adjusted odds ratio [OR]=2.250) and Qi-stagnation (adjusted OR= 3.824) constitutions were significantly associated with depression. Remote work during the outbreak (adjusted OR=1.920), decrease in income (adjusted OR=3.556), and disease progression (P=0.030) were associated with the occurrence of depression. Conclusion: Chinese patients with SSc have a high prevalence of depression and anxiety. The COVID-19 pandemic has changed the care patterns of Chinese patients with SSc, and work, income, disease progression, and change of medications were correlates of depression or anxiety in patients with SSc. Qi-stagnation and Qi-deficiency constitutions were associated with depression, and Qi-stagnation constitution was associated with anxiety in patients with SSc. Trial registration: ChiCTR, ChiCTR2000038796, Registered 02 October 2020, http://www.chictr.org.cn/showproj.aspx?proj=62301